Ambulatory blood pressure changes with lung ultrasound-guided dry-weight reduction in hypertensive hemodialysis patients: 12-month results of a randomized controlled trial. Issue 7 (July 2021) - Loutradis, Charalampos; Sarafidis, Pantelis A.; Ekart, Robert; Tsouchnikas, Ioannis; Papadopoulos, Christodoulos; Kamperidis, Vasileios; Alexandrou, Maria Eleni; Ferro, Charles J.; Papagianni, Aikaterini; London, Gerard; Mallamaci, Francesca; Zoccali, Carmine
Abstract : Objectives: Hypertension is highly prevalent and independently associated with adverse outcomes in patients undergoing hemodialysis. Volume overload is the main mechanism of increased blood pressure (BP) in these individuals. This study examines the long-term effects of dry-weight reduction with a standardized lung-ultrasound (US)-guided strategy on ambulatory BP in hypertensive hemodialysis patients. Methods: This is the report of the 12-month follow-up of a randomized controlled trial in 71 clinically euvolemic, hemodialysis patients with hypertension. Patients were randomized to dry-weight reduction guided by prehemodialysis lung ultrasound and to standard care. A 48-h ambulatory BP monitoring (ABPM) was performed in all study participants at baseline and after 12 months. Results: During follow-up, a greater proportion of patients in the active group underwent dry-weight reduction compared with the control group (71.4% vs. 22.2%; P < 0.001). The number of lung US-B lines (a metric of lung water) reduced in the active (−4.83 ± 13.73) and increased in the control arm (+5.53 ± 16.01; P = 0.005) paralleling dry-weight changes (−1.68 ± 2.38 vs. 0.54 ± 2.32 kg; P < 0.001). At 12 months, 48-h systolic BP (136.19 ± 14.78 vs. 130.31 ± 13.57 mmHg; P = 0.034) and diastolic BP (80.72 ± 9.83 vs. 76.82 ± 8.97 mmHg; P = 0.008) were lower compared to baseline in the active but similar in the control group. Changes in 48-h systolic BP (−7.78 ± 13.29 vs. −0.10 ± 14.75 mmHg; P = 0.021) were significantly greater in the active compared to the control group. The proportion of patients experiencing ≥1 episode of intradialytic hypotension was nominally lower in the active group (71.4% vs. 88.9%, P = 0.065). Conclusions: Lung-US-guided dry-weight reduction can effectively and safely decrease ambulatory BP levels in the long-term. Abstract : Supplemental Digital Content is available in the text